Analisis Pembinaan Karakter: Membangun Transformasi Insan Kamil Menurut Pemikiran Imam Al-Ghazali - Ariani, Rina; Ritonga, Mahyudin (UII Darullughah Waddawah Pasuruan, 2024)
Character development in Islamic education is an integral part of shaping a generation with strong faith and high morals. The thoughts of Imam Al-Ghazali, as one of the leading figures in the intellectual tradition of Islam, provide a strong foundation for the development of the concept of